IMPLEMENTASI EMPLOYEE RELATIONS DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN DI PT PLN AREA PEKANBARU - Lydiana Monika; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Employees are one part of the company's internal public which becomes the main element in achieving the goals. Employee relations is influrnced by internal relations between internal employees between leaders and employees with other employees or the relationship between employees and effective company manajement. The phenomena that occur in the new area of the company are lack of employees ability to carry out task oriented tasks, absenteeism problems, lack of respect for employee creativity, lack of communication between leaders and employees and careers running bogged down, monotounos and boring work. One the offorts made by PT PLN (Pesrero) Area Pekanbaru is to foster employee work through the application of employee relations to continue to produce the best and quality employees. This study aims to etermine the form of employee relations communication in increasing employee work motivation at PT PLN (Persero) Area Pekanbaru.This study uses qualitative methods with deskriptive analisis. The subjects in this study were determided based on a purposive technique consisting of public relations supervisors and company employees. Data collection techniques use Huberman’s interaktive style and Miles with the validity of the data being checked using an extension of participation and triangulation.The result of the study indicate that the form of employee relations at the PT PLN (Persero) Regional Pekanbaru plays a role in increasing employee work motivation at PT PLN (Persero) Regional Pekanbaru. The form of employee relations program that is implemented is education and training programs, award programs, special programs, employee welfare programs. The four programs that have been implemented are effective programs to increase employee motivasion at PT PLN regional Pekanbaru.Form of employee relations communication that is communication down, communication upwards, parallel communication. This form of employee relations communication is very influential in increasing employee motivation at PT PLN Regional Pekanbaru.Keywords: Implementation Employee Relations, Work Motivation